Effects of virtual reality on social participation after stroke: a systematic review - Queiroz, Letícia Costa; Menezes, Kênia Kiefer Parreiras de; Avelino, Patrick Roberto (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The cerebrovascular accident (CVA), or stroke, is characterized as a vascular injury occurring in the nervous tissue, in which there is interruption in the blood flow with consequent loss of the local supply of nutrients and oxygen, leading to tissue death. According to data from the Unified Health System and other studies, the CVA represents the greatest cause of death and permanent disability in Brazil. Objectives: The objective of this study was to perform a systematic review of the literature, searching for evidence of the effects of the use of the rehabilitation based on virtual reality to help recover the social participation of hemiparetic subjects after stroke. Methods: Searches were conducted on Medline, CINAHL, Web of Science, LILACS and PEDro databases, without restriction regarding the language and publication year of the study. The articles were evaluated by title, abstract and full text and, finally, selected in relation to the eligibility by two independent authors. The methodological quality of the included experimental studies was evaluated according to the PEDro scale. Results: Among the 11 articles included in the present review, only 4 demonstrated significant effects of virtual reality training on social participation/quality of life of hemiparetic subjects, when compared to the control group. Conclusion: The studies analyzed show that although there seems to be benefits of using virtual reality in global aspects of hemiparetic patient recovery, such as in motor function, the results are still not consistent regarding the social participation.